2020
DOI: 10.1155/2020/2092478
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Antimicrobial Resistance Profiles of Thermophilic Campylobacter Species in Humans and Animals in Sub-Saharan Africa: A Systematic Review

Abstract: Thermophilic Campylobacter species are clinically important aetiologies of gastroenteritis in humans throughout the world. The colonization of different animal reservoirs by Campylobacter poses an important risk for humans through shedding of the pathogen in livestock waste and contamination of water sources, environment, and food. A review of published articles was conducted to obtain information on the prevalence and antimicrobial resistance (AMR) profiles of thermophilic Campylobacter species in humans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 113 publications
3
54
0
Order By: Relevance
“…High isolation rates of C. jejuni (12.9%) were in agreement with those reported from Kolkata, Algeria [7] and Burkina Faso [24], but also closely compares with studies conducted in South Africa (20.3%), and Kenya (16.4%). In other studies, Nigeria reported the highest prevalence (62.7%) followed by Malawi (21%) [25]. The differences in age groups may also be the possible explanations for the variation of the results.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…High isolation rates of C. jejuni (12.9%) were in agreement with those reported from Kolkata, Algeria [7] and Burkina Faso [24], but also closely compares with studies conducted in South Africa (20.3%), and Kenya (16.4%). In other studies, Nigeria reported the highest prevalence (62.7%) followed by Malawi (21%) [25]. The differences in age groups may also be the possible explanations for the variation of the results.…”
Section: Discussionmentioning
confidence: 70%
“…The high percentage of multiple drug resistant Campylobacter jejuni to most frequently used antibiotics may be due to uncontrolled use of antibiotics such as selfmedicating and access to drugs without prescription [25,38]. Most of the time, acute gastroenteritis due to Campylobacter species will be treated empirically with fluoroquinolones and macrolides.…”
Section: Discussionmentioning
confidence: 99%
“…These results support previous reports of increased resistance to fluoroquinolones in C. jejuni strains from various sources, including chickens [ 57 ]. Campylobacter strains are becoming more resistant to drugs of choice, and this has been associated with the irrational use of various antibiotics in animal husbandry [ 58 ], mainly poultry [ 7 , 8 ]. Apart from the point mutation in gyr A, increased resistance to quinolones has been associated with the broad use of fluoroquinolones in the human population and veterinary medicine [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of human cases of campylobacteriosis has been increasing in many countries throughout the world [4,5]. In Africa, the prevalence varies from 7.7-18.5%, and Campylobacter is persistently found in stools of both diarrheic and non-diarrheic children [7,8,9], often associated with poor hygiene and sanitation [9].…”
Section: Introductionmentioning
confidence: 99%